Особливість лідерських якостей майбутніх менеджерів - Яценко, Ольга Миколаївна (Центр міжнародного наукового співробітництва, вид-во "ТК Меганом", 2016)
Наведено перелік ключових лідерських якостей майбутніх менеджерів у дослідженнях вітчизняних і зарубіжних науковців. Виділено комплекс основних лідерських якостей, які повинні бути в успішного менеджера-лідера.

The article provides the list of key leadership skills of future managers in the research of Ukrainian and foreign scientists. The paper determines a set of basic leadership qualities to make a successful leading manager. It is proposed to consider it to have a double-stage structure. A list of leadership qualities that are specific to the activities of managers has been made. The criteria of their formation which would allow to observe the process in progress. It has been determined that certain leader qualities can be formed in the psycho-pedagogical training when studying at university.
Feature leadership qualities of future managers
Keywords: менеджери; лідерські якості; лідерство; комунікативність; рефлексивність; організаторські здібності; професійні якості; leadership; managers; communicative; reflexivity; organizational skills; success